Πετρολογική - ορυκτολογική μελέτη των μεταβασιτών (πρασινιτών) της Λαυρεωτικής γεωτεκτονικό περιβάλλον σχηματισμού τους - ARIKAS, Κ.; PAPE, Μ.; ΣΕΡΕΛΗΣ, Κ.; ΤΣΑΓΚΑΛΙΔΗΣ, Α. (Bulletin of the Geological Society of Greece, 2001)
The SE part of Attica belong to the Attico Cycladic massif and comprises gneiss, quartzites series of marble and scists, metabasites and metaultrabasites. The metabasites (prasinittes) of Laurium area recognized in over 60 outcrops. The main mineral of the metabasites are actinolites, actinolitic hornblende glaucophan frequently altered to chlorite, albite, epidot - clinozoisite and chlorite which in the most frequent mineral. According to the mineral composition those metabasites have been affected by an intermediate to high temperature green - schist metamorphic phase. Nevertheless the presence of glaucophane shows that a high pressure metamorphic phase under subduction conditions was preceded. The detailed study of distinctive classification diagrams based on the main and trace elements of the Laurium prassinites showed a subalkalic basaltic character. The geotectonic environment of thoss basaltic magmas should be of MORB type with a tholeiitic character belonging the E or PMORB type basalts